Russian Anarchists - Avrich, Paul (Book collections on Project MUSE., 2015)
Professor Avrich records the history of the anarchist movement from its Russian origins in the 19th century, with a full discussion of Bakunin and Kropotkin, to its upsurge in the 1905 and 1917 Social Democratic Revolutions, and its decline and fall after the Bolshevik Revolution. While analyzing the role of the anarchists in these fateful years, he traces the close relationships between the anarchists and the Bolsheviks and shows that the Revolutions were conceived in spontaneity and idealism and ended in cynical repression. The Russian anarchists saw clearly the consequences of a Marxist "dictatorship of the proletariat" and, though they had no single cohesive organization, repeatedly warned that the Bolsheviks aimed to replace the tyranny of the tsars with a tyranny of commissars. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.